The management of youth employment in a lifelong engineering education system; International Review of Management and Marketing; Vol. 6, iss. 2S - Morozova M. V. Marina Vyacheslavovna; Kust T. S. Tatiana Sergeevna; Sokolova E. Ya. Elvira Yakovlevna; Osipova S. I. Svetlana Ivanovna; Gafurova N. V. Nataliya Vladimirovna; Vaganova V. I. Valentina Ivanovna; Ovchinnikov V. A. Vladimir Alekseevich; Agavelyan R. O. Ruben Oganesovich (2016, 2016)
Title screen